(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article explores the concept of artistic metamorphosis, its poetic process, forms and types on the example of examples of the narrative genre. Also, the historical and theoretical features of the phenomenon of artistic metamorphosis, the syncretic basis are discussed in detail in the story and the story. In the story, the form of spiritual metamorphosis of artistic metamorphosis is analyzed. Alisher Navoi’s story "Hazrati Ayyub and the thief" and Ghafur Ghulam’s "My Thief Boy" show metamorphosis as an object of artistic representation.